Implementasi Teknik Relaksasi Otot Progresif pada Penderita Ostepororosis di Desa Bangun Rejo Kecamatan Tanjung Morawa Provinsi Sumatera Utara Tahun 2025 - Petra Diansari Zega; Ali Imran Sirait; Eko Murdianto; Sri Muliati Nendah; Nurcahaya Sihombing (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Osteoporosis is a type of bone metabolism disorder in which bone density decreases, leading to porous and fragile bones that are easily fractured. The risk factors for osteoporosis include increasing age (over 60 years) and gender (more common in women). The clinical manifestations experienced by individuals with osteoporosis include back pain. One of the interventions that can be implemented to reduce pain is progressive muscle relaxation. This study employed a quasi-experimental design. The population and sample consisted of 28 elderly individuals divided into two groups: the experimental group and the control group. The results showed that after progressive muscle relaxation was performed, there was a significant effect in reducing pain in the experimental group, with a p-value of 0.040.